REALIZING INCLUSIVE NAHWU LEARNING AMID STUDENT DIVERSITY - Tauhid, Tauhid; Salam, Muhammad Yusuf; Basri, Hasan; Ibrahim, Abdullah Umar Al Haj (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to identify the challenges in learning Nahwu at STAIN Mandailing Natal and to explore inclusive learning strategies that accommodate the diverse educational backgrounds of students. Such diversity, which includes students from Islamic boarding schools, madrasahs, and general schools, affects their level of understanding and motivation in studying Nahwu. The research employed a qualitative approach with data collected through semi-structured interviews, classroom observations, questionnaires, and document analysis. The findings reveal that students from general school backgrounds face greater difficulties in comprehending Nahwu material, whereas those from Islamic boarding schools demonstrate stronger prior knowledge. Inclusive learning strategies, such as the use of visual media and cross-background study groups, were found effective in enhancing students’ comprehension. However, challenges remain in implementing supplementary guidance outside the classroom. This study concludes that Nahwu learning needs to be designed in a more inclusive, adaptive, and responsive manner to meet the diverse needs of students, ensuring that the learning process becomes more effective and equitable.